Resistance Mutations in gyrA and parC are Common in Escherichia Communities of both Fluoroquinolone-Polluted and Uncontaminated Aquatic Environments - Johnning, Anna; Kristiansson, Erik; Fick, Jerker; Weijdegård, Birgitta; Larsson, D. G. Joakim (Frontiers in Microbiology, 2015)
Alterations in the target proteins of fluoroquinolones, especially in GyrA and ParC, are known to cause resistance. Here, we investigated environmental Escherichia communities to explore the possible link between the abundance of mutations, and the exposure to fluoroquinolones. Sediment samples were collected from aquatic environments representing a range from non-polluted up to 1 mg fluoroquinolones/g organic matter. The quinolone resistance-determining regions of gyrA and parC were analyzed using amplicon sequencing of metagenomic DNA. Five non-synonymous substitutions were present in all samples, and all of these mutations have been previously linked to fluoroquinolone resistance in E. coli. In GyrA, substitutions S83L and D87N were detected at frequencies of 86% and 32%, respectively, and 31% of all amplicons encoded both substitutions. In ParC, substitutions S80I, E84G, and E84V were detected in 42%, 0.9%, and 6.0% of the amplicons, respectively, and 6.5% encoded double substitutions. There was no significant correlation between the level of fluoroquinolone pollution and the relative abundance of resistance mutations, with the exception of the most polluted site, which showed the highest abundance of the aforementioned substitutions in both genes. Our results demonstrate that resistance mutations are common in environmental Escherichia, even in the absence of a fluoroquinolone selective pressure.